Stability of patterns of apparent electrical conductivity in dry versus wet soil conditions - Serrano, João (2012)
The general objective of this study was to evaluate the stability of patterns of apparent electrical conductivity (ECa) in dry versus wet soil conditions in shallow soils, typically used for pastures in Mediterranean conditions of southern region of Portugal. The statistical analysis of apparent electrical conductivity resulted in a significant correlation coefficient (R = 0.88) between dry and wet soil conditions. A multi-variate regression was carried out using the parameters that show greater correlation with ECa: P, K, organic matter, pH, relative elevation and clay content. The results show, in dry and wet conditions, that the effect is significant (R=0.79 and R=0.82, respectively). This indicates the temporal stability of ECa patterns under different soil moisture contents, which is relevant with respect to the time when a field should be scanned and is important for using ECa as a decision support tool in precision agriculture.